The popular encyclopedia of apologetics - Hindson, Edward E.; Caner, Ergun Mehmet (Eugene, Or. : Harvest House Publishers, 2008)
"As a Christian, are you ready to answer the questions people have about God, Jesus Christ, and your faith? That's not an easy task in today's world. You'll find The Popular Encyclopedia of Apologetics a helpful guide to responding to even the most difficult questions with clarity and confidence. With more than 175 articles and 55 expert contributors (including Christian converts from some of the belief systems discussed), this volume provides the most current essentials you need to know about a wide variety of apologetic concerns, including: critical issues related to God, Christ, the Spirit, and the Bible; scientific and historical controversies (including creationism and biblical inerrancy); ethical matters (including abortion, stem cell research, and homosexuality); a Christian response to major world religions and cults; a Christian response to major worldviews and secular philosophies"--Back cover.
Abortion -- Adoptionism -- Agnosticism -- Analogy of Being -- Animism -- Anselm of Canterbury -- Apocrypha -- Apollonarianism and Nestorianism -- Apologetics, Biblical -- Apologetics, Biomedical -- Apologetics, Creation -- Apologetics, Cult -- Apologetics, Cultural -- Apologetics, Dispensational -- Apologetics, Ethical -- Apologetics, Global -- Apologetics, Historical -- Apologetics, Incarnational -- Apologetics, Philosophical -- Apologetics, Prophetic -- Apologetics, Reformed -- Apologetics, Scientific -- Apologetics, Types of -- Aquinas, Thomas -- Archaeology, Biblical -- Arianism -- Asian Folk Religion -- Astrology -- Athanasius -- Atheism -- Atonement -- Augustine of Hippo -- Baha'i -- Behaviorism -- Bible, Alleged Errors -- Bible, Canonicity -- Bible, Inerrancy of -- Bible, Transmission of -- Biblical Criticism -- Buddhism -- Chopra, Deepak -- Christ, Crucifixion of -- Christ, Divinity of -- Christ, Exclusivity of -- Christ, Historicity of -- Christ, Humanity of -- Christ, Miracles of -- Christ, Resurrection of -- Christ, Uniqueness of -- Christ, Virgin Birth of -- Christian Identity Aryanism -- Christian Science -- Church Councils -- Confucianism -- Creation, Theories of -- Cults, Characteristics of -- Dead Sea Scrolls -- Death, Theories of -- Deism -- Descartes, Rene -- Determinism -- Devils and Demons -- Divorce -- Docetism -- Dualism -- Eastern Orthodoxy -- Ebionites -- Embryonic Stem Cell Research -- Empiricism -- Enlightenment, Age of -- Ethics, Business -- Ethics, Christian -- Euthanasia -- Evangelism -- Evidentialism -- Evil, Problem of -- Evolution, Theory of -- Existentialism -- Feminism -- Fideism -- Foundationalism -- Genetic Ethics -- Gnosticism -- God, Existence of -- God, Foreknowledge of -- God, Gender of -- God, Image of -- God, Immanence and Transcendence -- God, Nature and Attributes of -- Grace -- Hedonism -- Henry, Carl -- Hinduism -- Holy Spirit, Role in Apologetics -- Homosexuality -- Immortality -- Irenaeus -- Islam -- Islam, Nation of -- Israel and Replacement Theology -- Jainism -- Jehovah's Witnesses -- Jesus Seminar -- Judaism -- Kabbalah -- Kant, Immanuel -- Kierkegaard, Soren -- Knowledge, Theories of -- Language -- Lewis, C.S. -- Liberalism -- Life After Death -- Logical Fallacies -- Lost Gospels, The -- Love -- Marriage -- Martyr, Justin -- Marxism -- Mind Science -- Monism -- Monophysitisrn -- Moral Law -- Mormonism -- Mysticism -- Mythology -- Occult -- Oneness Pentecostalism -- Open Theism -- Origen -- Paganism -- Pain and Suffering -- Paley, William -- Pantheism -- Pascal, Blaise -- Pelagianism -- Pluralism -- Polytheism -- Postmodernism -- Presuppositionalism -- Preterism -- Psychology and Faith -- Reason and Faith -- Reconstructionism, Christian -- Reincarnation -- Relativism -- Revelation, General and Special -- Roman Catholicism -- Salvation, Exclusivity of -- Salvation, Theories of -- Schaeffer, Francis -- Science and Faith -- Science Fiction and UFO Cults -- Secular Humanism -- Seventh-day Adventism -- Sikhism -- Sin -- Socinianism -- Socratic Philosophers -- Soul -- Suicide -- Taoism -- Tertullian -- Theosophy -- Tolerance -- Trinity -- Tritheism -- Truth, Theories of -- Unification Church -- Universalism -- Van Til, Cornelius -- War -- Wicca -- William of Ockham -- Worldvicw -- Zen Buddhism -- Zoroastrianism.
Includes bibliographical references.
Keywords: Apologetics -- Encyclopedias